Modeling Wave Energy Dissipation by Bottom Friction on Rocky Shores - César Acevedo-Ramirez; Olavo B. Marques; Falk Feddersen; Jamie H. MacMahan; Sutara H. Suanda (Journal of Marine Science and Engineering, 2026)
Rocky shores are characterized by rough, multi-scale bathymetric variations that result in enhanced wave energy dissipation by bottom friction compared to sandy beaches. Realistic SWAN simulations of surface gravity waves across the rocky shores of Monterey (CA, USA) are conducted, and model results are compared to 20 inner-shelf observational sites spanning 34–5 m water depth. The wave field was highly variable during the study, including alternately low energy waves dominated by southern swell and higher energy local waves aligned with strong north-westerly winds. Including a modified bottom friction parameterization is required for the model to reproduce bulk wave statistics with high skill across the entire inner shelf. The SWAN simulation with the default bottom friction parameterization overestimates significant wave height relative to observations because the friction factor fe parameterization has a maximum value of 0.3. Additional simulations included two empirical formulations relating fe to the normalized wave excursion Ab/kN in the large roughness regime Ab/kN

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Erratum to: Carriers of genetic variants in the HNF1A gene are more common among dead opioid addicts than among living addicts - Anh Nguyen; Tore B. Stage; Søren Feddersen; Dorte J. Christoffersen; Mette Marie H. Christensen; Per Damkier; Jørgen L. Thomsen; Kim Brøsen (European Journal of Clinical Pharmacology, 2017)

Carriers of genetic variants in the HNF1A gene are more common among dead opioid addicts than among living addicts - Anh Nguyen; Tore B. Stage; Søren Feddersen; Dorte J. Christoffersen; Mette Marie H. Christensen; Per Damkier; Jørgen L. Thomsen; Kim Brøsen (European Journal of Clinical Pharmacology, 2016)

Measuring Fluorescent Dye in the Bubbly and Sediment-Laden Surfzone - David B. Clark; Falk Feddersen; Melissa M. Omand; R. T. Guza (Water, Air, & Soil Pollution, 2009)

Egg release and settlement patterns of dioecious and hermaphroditic fucoid algae during the tidal cycle - L. B. Ladah; F. Feddersen; G. A. Pearson; E. A. Serrão (Marine Biology, 2008)

Acyl-CoA binding proteins; structural and functional conservation over 2000 MYA - Nils J. Færgeman; Majken Wadum; Søren Feddersen; Mark Burton; Birthe B. Kragelund; Jens Knudsen (Molecular and Cellular Biochemistry, 2007)

BUBBLE – an Urban Boundary Layer Meteorology Project - M. W. Rotach; R. Vogt; C. Bernhofer; E. Batchvarova; A. Christen; A. Clappier; B. Feddersen; S.-E. Gryning; G. Martucci; H. Mayer; V. Mitev; T. R. Oke; et al. (Theoretical and Applied Climatology, 2005)